Using public expenditure tracking surveys to monitor projects and small-scale programs : a guidebook - Koziol, Margaret (World Bank e-Library., 2010)
Public Expenditure Tracking Surveys (PETS) are a tried and tested methodology to identify delays in financial and in-kind transfers, leakages, and other inefficiencies in government programs. This guidebook aims to provide a starting point for civil society groups and other organizations interested in taking a closer look at government spending processes, both on a small and a larger scale. It is designed to lead users from the definition of the appropriate Public Expenditure Tracking Survey to be used, to the dissemination of its findings, with an emphasis on using evidence effectively to influence policy decisions at any level. Based on the experience of the World Bank in measuring and improving the effectiveness of service delivery, this approach helps empower citizens to keep service providers accountable through better information, communication, and engagement.